A qualitative study exploring the experience of people with IBD and elevated symptoms of anxiety and low mood and the type of psychological help they would like. Issue 5 (4th May 2018) - Jordan, Cheryl; Ohlsen, Ruth; Hayee, Bu'Hussain; Chalder, Trudie
Abstract : Background: People with inflammatory bowel disease (IBD) are at increased risk of developing anxiety and low mood. We sought to explore the experience of people with IBD and moderate–severe symptoms of anxiety/low mood to identify psychological processes which could be targeted in psychological interventions, as well as the kind of psychological support preferred. Methods : Twenty-five participants with IBD and moderate–severe symptoms of anxiety/low mood were recruited for interview. Template analysis was utilised to analyse interview data. We explored the situations, cognitions and behaviour linked to symptoms of anxiety and low mood by people with IBD, as well as the kind of psychological help preferred. Results: Two themes were identified within participants accounts of symptoms of anxiety; 'under performance' and 'preventing an accident'. Two further themes were identified for symptoms of low mood; 'lack of understanding' and 'stigma'. Expertise and understanding was the main theme identified for the type of psychological help desired. Conclusion: The analysis highlights situations, cognitions and behaviour linked to anxiety and low mood by people with IBD and the type of psychological support desired. Our findings link to the knowledge and competencies set for psychological therapist working with long-term conditions.